Spoof Plasmon Surfaces: A Novel Platform for THz Sensing. Issue 8 (7th June 2013) - Ng, Binghao; Wu, Jianfeng; Hanham, Stephen M.; Fernández‐Domínguez, Antonio I.; Klein, Norbert; Liew, Yun Fook; Breese, Mark B. H.; Hong, Minghui; Maier, Stefan A.
<x xml:space="preserve">Abstract</x> Spoof plasmon surfaces consisting of linear arrays of subwavelength grooves are proposed as a novel platform for THz sensing. The tightly confined spoof plasmons, coupled via an Otto prism setup, are sensitive to the refractive index of the dielectric filling the grooves. Phase jumps at spoof plasmon resonances are used as a readout response for refractive index sensing. An overall sensitivity of 0.49 THz RIU−1 with figures‐of‐merit as high as 49 are achieved. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>